Immunogenicity and performance of an enterovirus 71 virus-like-particle vaccine in nonhuman primates. Issue 44 (4th November 2015) - Lim, Pei-Yin; Hickey, Andrew C.; Jamiluddin, Mohamad F.; Hamid, Sharifah; Kramer, Joshua; Santos, Rosemary; Bossart, Katharine N.; Cardosa, M. Jane
Highlights: A novel bicistronic EV-A71 P1 and 3CD expression cassette has been developed. Highly native EV-A71 virus-like particles were made using the bicistronic cassette. Purified EV-A71 virus-like particles were highly immunogenic in nonhuman primates. Vaccination with EV-A71 virus-like-particles protected animals from EV-A71 challenge. This is the first EV-A71 virus-like-particle efficacy study done in nonhuman primates. Abstract: A vaccine against human enterovirus 71 (EV-A71) is urgently needed to combat outbreaks of EV-A71 and in particular, the serious neurological complications that manifest during these outbreaks. In this study, an EV-A71 virus-like-particle (VLP) based on a B5 subgenogroup (EV-A71-B5 VLP) was generated using an insect cell/baculovirus platform. Biochemical analysis demonstrated that the purified VLP had a highly native procapsid structure and initial studies in vivo demonstrated that the VLPs were immunogenic in mice. The impact of VLP immunization on infection was examined in non-human primates using a VLP prime-boost strategy prior to EV-A71 challenge. Rhesus macaques were immunized on day 0 and day 21 with VLPs (100 μg/dose) containing adjuvant or with adjuvant alone (controls), and were challenged with EV-A71 on day 42. Complete blood counts, serum chemistry, magnetic resonance imaging (MRI) scans, and histopathology results were mostly normal in vaccinated and control animals after virus challenge demonstrating that the fatal EV-A71-B3 clinical isolate used in this study was not highly virulent in rhesus macaques. Viral genome and/or infectious virus were detected in blood, spleen or brain of two of three control animals, but not in any specimens from the vaccinated animals, indicating that VLP immunization prevented systemic spread of EV-A71 in rhesus macaques. High levels of IgM and IgG were detected in VLP-vaccinated animals and these responses were highly specific for EV-A71 particles and capsid proteins. Serum from vaccinated animals also exhibited similar neutralizing activity against different subgenogroups of EV-A71 demonstrating that the VLPs induced cross-neutralizing antibodies. In conclusion, our EV-A71-B5 VLP is safe, highly immunogenic, and prevents systemic EV-A71-B3 infection in nonhuman primates making it a viable attractive vaccine candidate for EV-A71.